Dermatology in the military field: What physicians should know? - Chong, Wei-Sheng (Baishideng Publishing Group Co., Limited, 2013)
In the civilian dermatological setting, the top 5 skin diseases usually seen are eczema/dermatitis, acne, benign skin tumors, viral infections and pigmentary disorders. In comparison, the top 5 skin conditions encountered in the military sector are usually fungal infections, eczema/dermatitis, insect bite reactions, bacterial infections and acne. This is not surprising as military personnel, due to the special environment and vocations they are in, are prone to getting eczema as heat, sweating and wearing of the military uniform aggravate the condition. Fungal infections are common in those who wear the army boots. Insect bite reactions are not an uncommon sight among those who have to go to the jungle regularly for outfield training. Grass allergy or intolerance, contact dermatitis or acneiform eruption due to the application of military camouflage cream on the face, contact dermatitis to insect repellents, and military uniform allergy and intolerance are amongst the commonest dermatological problems encountered in the military field, and physicians should recognize them, investigate and manage these problems accordingly. Lastly, a diagnosis not to be missed in the military field is cutaneous melioidosis, especially when a military personnel presents with a non-healing ulcer.